Екстраполяційний метод чисельного розв'язання задачі Коші для звичайних диференціальних рівнянь та їхніх cистем - Лещишин, Наталя (Видавництво Національного університету «Львівська політехніка», 2009)
The new approach to construction of the apparatus of Non-Classical Newtonian Majorants and Diagrams functions given tabulary has been used for construction new numerical methods extrapolation type of solving the Cauchy problem both for ordinary differential equations ans systems of ordinary differential equations. The convergence and calcu lating stability of the methods has been proved.
Keywords: differential equations; numerical methods; Cauchy problem